Effect of α-Tocopherol on Viability, Lipid Peroxidation and Oxidative Stress of Cryopreserved Ovine Preantral Follicle - Kaushik, Kalpana; Pulukuri, Johnson; Tej, NikhilK; Krishna, Kavya; Gupta, Paluru S.P.; Nandi, Sumanta; Mondal, Sukanta (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Vitrification of preantral follicles is a promising technique to preserve female fertility. The aim of the present study was to evaluate the effect of supplementation of α-tocopherol in the vitrification solution on the viability, lipid peroxidation and mRNA expression of superoxide dismutases (SOD1 and SOD2) in vitrified cultured ovine preantral follicles at day-6 and day-12. Preantral follicles (200-300 µm) were isolated from the ovine ovaries by the mechanical method and were distributed separately to the vitrification medium supplemented with 10 mM and 20 mM of α-tocopherol.  After a week, the follicles were thawed and analyzed for follicular viability by trypan blue dye exclusion method and subjected to in vitro culture (IVC) for 6 and 12 days. Our results revealed that the significant increase (p
Keywords: Ovary; Preantral follicles; Vitrification; α-tocopherol; Sheep; Gene